Anomaly and geochemistry of rare earth elements and yttrium in the late Permian coal from the Moxinpo mine, Chongqing, southwestern China - Jianhua Zou; Dong Liu; Heming Tian; Tian Li; Feng Liu; Lin Tan (International Journal of Coal Science & Technology, 2014)
Abstract The rare earth elements and yttrium (REY) of the K2 coal from the Moxinpo mine, Chongqing, were determined using inductively coupled plasma mass spectrometry (ICP-MS). The results show that REY are enriched in the K2 coal, with the average content up to 462 μg/g, much higher than average values of most coals in the world. The REY distribution patterns indicate that the light REY is enriched and show a well-pronounced Eu minimum. The fractionation of individual light-REY is higher than that of the heavy-REY. The REY distribution through the K2 coal seam shows that the top and bottom portion of the coal seam have a lower content of REY than the middle portion. Goyazite and rhabdophane were identified with a scanning electron microscope equipped with an energy-dispersed X-ray spectrometer (SEM-EDX). The REY distributions through the coal seam, SEM-EDX data and the correlation analysis between ash yields and the concentrations have revealed that the REY mainly occurs in the organic matter. The K2 coal is a potential rare-metal resource due to its high REY contents, and the coal ash could be regarded as a new and promising raw material for recovery of REY as a by-product.